Understanding Khawarij Ideology as an Effort for Early Detection of Terrorism Actions - Ghofur, Abdul; Priyanto; Agus H.S. Reksoprodjo (Indonesian Journal of Applied and Industrial Sciences (ESA), 2025)
Terrorism is globally recognized as a serious threat to the security and stability of a country. In the context of Indonesia, terrorism is defined as an actual threat, namely a threat that is currently developing and will continue in the next few years. Based on the history of the development of terrorism in Indonesia, extreme Muslim groups are often found as perpetrators of terrorism in Indonesia. Some of them are affiliated with international terrorism networks such as Al-Qaeda and the Islamic State of Iraq and Syria (ISIS). This group believes that it is permissible to kill anyone who disagrees with their views. This group is known as Khawarij. The special characteristic of the Khawarij group is that they adhere to the Takfiri ideology, namely declaring those who do not follow the beliefs or practices of the religion they adhere to as infidels. In its development, the Khawarij ideology became the ideological root of extremist movements among Muslims. The relationship between the Khawarij ideology and current acts of terrorism lies in the excessive understanding of Islam, as well as the justification of violence against other groups under the pretext of religion. Khawarij ideology also believes that a leadership (government) that does not implement Islamic laws is an infidel government that must be fought. These radical doctrines have led to the emergence of new extremist movements such as Al-Qaeda and ISIS. Therefore, one strategy in preventing acts of terrorism is to conduct Early Detection of the understanding of Khawarij ideology as part of the Early Warning System.